ASSESSING THE CASUAL RELATIONSHIP BETWEEN PARENTAL ASPIRATION AND ACADEMIC PERFORMANCE OF THEIR CHILDREN - P. Nicola Prakash, Dr. Arockia Mary.R (International Journal of Advanced Science and Technology, 2020)
The paper tries to lime light the importance of extrinsic parental aspirational factors and its influential role on the academic performance of their children. Though the parents aspiration has a greater influence on the academics of their children, this paper tries to work with the extrinsic relational aspects of parental aspiration that has correlation with the education.